Pendayagunaan Media Pembelajaran untuk Memaksimalkan Kompetensi PAI - Hilyah Ashoumi (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2017)
The effectiveness of communication in the teaching and learning activity is when the students are able to draw meaning of information they have received. The use of learning source of media have an important role to increase students competence especially PAI. The students knowledge will not be verbal, they ara able to internalize and apply in attitude and behavior as spiritual and social. The media as intermediaries can cause same meaning as message between teacher and students, so that the learning can be communicative. In maximizing PAI learning and reaching the goal, it needs many considerations in choosing media, such as 1) the media should be accurate and representative, 2) the interaction gained, 3) the special ability media posses, 4) degree of motivation, 5) and the cost needed.